Characterisation of Polycrystalline Cubic Boron Nitride Tool Materials - Lindgren, Kristina (My University, 2013)
The reactions that occur during sintering of polycrystalline cubic boron nitride composite (PCBN) tool materials and their dependence on starting powder composition have been mapped. The starting powder mixtures of the PCBN composites consist of cBN, Ti(C,O,N), Al, and milling body debris. Two different types of milling bodies were used, WC-Co and cermet ((Ti,W)(C,N) grains in a Co binder phase). The PCBN materials were investigated before sintering, after pre sintering (900 C) and after high pressure high temperature sintering (1400 C) in order to understand the processes taking place. Methods used were XRD and SEM/XEDS. The Al was found to melt during the pre sintering and react with either W or Co. Among the phases found in the high pressure high temperature sintered materials were cBN, Ti(C,O,N), (Ti,W)(C,O,N), AlN, TiB2, WC, Al2O3, W2CoB2 and two unidentified phases.
Keywords: Grundläggande vetenskaper; Materialteknik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Materialvetenskap; Basic Sciences; Materials Engineering; Sustainable Development; Innovation & Entrepreneurship; Materials Science